The Development of a Recovery-Oriented Mental Health System in Canada: What the Experience of Commonwealth Countries Tells Us - Piat, Myra (Can J Commun Ment Health, 2009)
This article examines how the recovery concept has been introduced into national mental health policies in New Zealand, Australia and the England. Five overall themes are identified as critical in shifting to a recovery-oriented system: restructuring of mental health services; promoting mental health and preventing mental illness, developing and training the workforce; cultivating consumer participation and leadership and establishing outcome-oriented and measurable practices. These issues are vital in the uptake of recovery and should guide the overall direction of the Canadian Mental Health Commission’s mental health strategy.